Plano de projeto: construção de duas casas populares com estrutura geminada - Buzanelo, Helena (Universidade do Vale do Rio dos Sinos, 2012)
This work has as main objective to present a project plan for planning, management and execution of two semi-detached houses. The project is aligned with the practices used by the PMBOK (Project Manegament Body of Knowledge, 4th edition, 2009), because its focus on qualification and optimization of processes related to project management and construction processes as well as creating methods, tools and adequate infrastructure. This paper presents the project management plan, containing plans of management integration, scope, time, cost, quality, resources, communications, risk and acquisitions, necessary for the proper practice of project management.
Keywords: Plano de gerenciamento do projeto; Projeto e execução; Project management planning; Project and execution